jurnal PENGARUH VARIETAS DAN JENIS TANAH TERHADAP HASIL CABAI (Capsicum sp.) - Erfyana Putri, Elsha; Heru Pamungkas, Djoko; Arnanto, Driska (Universitas Sarjanawiyata Tamansiswa, 2025)
This research aims to determine the effect of variety and soil type on chili growth. This research was conducted at the Self-Help Agricultural and Rural Training Center (PAS)